The Effect of Outdoor Education Through Hiking and Camping on Confidence - Vania Utami; Indra Safari; Adang Sudrazat (JUARA : Jurnal Olahraga, 2022)
Education, in general, has a meaning as a life process in developing each individual to live and carry out daily life. Each student has a different environment and background, which affects their personality and the formation of their self-confidence and interaction with or environment. Self-confidence will arise if there is a need to be respected and appreciated because this will grow the strength, ability, and feeling of being valuable that other people need. This study aims to determine outdoor education through hiking and camping on self-confidence. The research method used is an experimental design with a pretest, post-test two experimental design. The sample in this study was 39 students divided into two groups at SMA PGRI 1 Subang; the data collection technique used a questionnaire. This study revealed that the average results of self-confidence increased, outdoor education can increase self-confidence, and it is recommended to be part of student education in schools.